The theory and practice of ageing housing transformation in China and abroad: a review / Zhang Junli ... [et al.] - Junli, Zhang; Hj Shanat, Musdi; Xiaoyuan, Ma X; Yen, Khong Heng (Universiti Teknologi MARA, Sarawak, 2013)
This paper investigates the theoretical research and practical exploration in housing the ageing in western developed countries and China after France first entered the ageing society. The subject of housing the ageing was reviewed using the methods of literature search and induction analysis. In terms of practical exploration, three basic models of ageing adaptation in developed countries were extracted: public welfare policy, nursing insurance system, and market economy. The objectives, objects, contents, advantages, and disadvantages of the transformation were analysed; the practical exploration and problems encountered in China's pilot cities for ageing adaptation were summarized. Through comparative analysis, it is proposed that we should learn from the advanced experience of western countries to avoid their shortcomings.